Economic viability of mechanization service provision for rice cultivation: A case study of small and medium enterprises in Cote d'Ivoire - Mahe Franck Marcel Guei; Wiyao Banakinaou; Moussa Bakayoko; Hideo Hasegawa (Scientific African, 2025)
Rice cultivation is integral to food security and economic development in Cote d’Ivoire; however, the widespread adoption of mechanization is constrained by high costs and logistical challenges in the country. This study evaluates the economic performance of Small and Medium Enterprises mechanization service providers involved in rice cultivation through a break-even analysis conducted across three distinct districts: Northern, Central, and Mountains. Utilizing real-world operational data, this study examined the profitability of various mechanization services, including plowing, harvesting, and threshing, under both optimal and actual working conditions. It assesses cost structures, including fixed and variable expenditures, effective field capacity, seasonal workday limitations, and regional service demand. The findings revealed significant variations in profitability by machinery type and location. Combine harvesters and tractors with rotovators, which are highly profitable in the central districts, have break-even points at 171.9 ha and 83.5 ha, respectively, achieving profit margins of 19 % and 8 %. Conversely, service providers in the northern districts encounter higher break-even thresholds, necessitating, for instance, a combine harvester and tractors with rotovators to service over 555.3 ha and 191.3 ha, respectively, to achieve profitability, which is hindered by dispersed demand and operational constraints. This study underscores the necessity of scale-appropriate mechanization, improved infrastructure, operator training, and supportive policies to enhance service viability. The policy recommendations, include subsidized leasing, shared-service models, and diversification of machinery, use beyond rice to ensure sustainable operations. These insights are crucial for informing the expansion of mechanization services through private sector engagement, offering a pathway to resilient and inclusive agricultural development in Cote d’Ivoire.